Variability in forewing venation patterns and genital shapes among four populations of Rice Black Bugs, Scotinophara coarctata (Fabricius) from Mindanao, Philippines - Torres, Mark Anthony J.; Yañez, Geoffrey Reuel Q.; Mahinay, Chistine Lovelle A.; Ong, Gerald Manuel P.; Esencia, Jay Ar O.; Martinez, Joey Genevieve T.; Tabugo, Sharon Rose M.; Adamat, Liza A.; Manting, Muhmin Michael E.; Joshi, Ravindra C.; Barrion, Alberto T.; Sebastian, Leocadio S.; et al. (2011)
Rice Black Bugs are small, cryptic, and highly invasive pest species attacking all growth stages of rice plant. This pest is extremely variable in morphology resulting to problems in its taxonomy. The present study reports on variability in wing venation pattern and genital plates among four populations of RBBs comprised of 1,149 males and 1,164 females from Tacurong, Sultan Kudarat (44M, 45F), Lala, Lanao del Norte (132F, 102M), Sta. Josefa, Agusan del Sur (216M, 216F), and Kabacan, North Cotabato (150F, 150M). Results showed immense inter-individual variability in venation patterns among the populations. The most importnt variations are in the type and number of marginal cells on the anterior distad part of the wing. The marginal cells are either closed or open and vary in number from 1-6. Geometric Morphometric anaylses revealed considerable differences in the shapes of the genital plates of both sexes (@&: Wilk's Lambda: 0.0005, P: <0.000; B&: Wilk's Lambda: 0.0009, P:<0.000). Results showed differences in the concavity of the anterior and postero-lateral margins of the genital plates. The results of the current study may indicate possible genetic differentiation. Such variability may have direct bearing on the management of the RBB as a pest of rice agroecosystem.
Keywords: Rice bug; Rice disease and pest resistance